Media Pembelajaran Berbasis Multikultural - Kharis, Muh. (Institut Agama Islam Negeri (IAIN) Tulungagung, 2014)
Multi cultural based teaching media is helpful for teacher and students during the process of teaching and learning. These media answer questions related to the establishment of multicultural education in Indonesian context which is not yet optimally carried out. With the help of multicultural based media, students are taught to understand the differences among their cultural background andÂ understand plurality as well.